The influence of utilising Facebook on e-government adoption - (:unkn) unknown (Inderscience Publishers, 2019)
E-government is becoming a major channel for citizens' communication, interaction and collaboration with their government. Utilising the increased use of social media, individuals, businesses and governments recognised the opportunity to benefit from these sites to open channels of communication and empowerment. In this paper, we measure the influence of social networks represented by Facebook on e-government in Jordan. We extended UTAUT2 with personal innovativeness and yielded a full support of all hypotheses assumed. Performance expectancy, social influence, effort expectancy, personal innovativeness and enjoyment significantly predicted the continuous use of e-government pages on Facebook. The estimated coefficient of determination R2 was 0.48. Conclusions are stated at the end. © 2019 Inderscience Enterprises Ltd.
Keywords: e-government; electronic government; Facebook; Government 2.0; ICT; Jordan; social media; social networks; UTAUT2; Web 2.0